Urban vs. rural: Contrasting environmental concerns and sustainable practices in the Romanian HoReCa sector - Paraschiv, Gabriela Iuliana; Stan, Mari-Isabella (Technium Social Sciences Journal, 2023)
This research questions the alignment of economic objectives with environmental management in the Romanian hospitality, restaurant and café (HoReCa) sector, with a focus on sustainable development. It juxtaposes the sector’s sustainability imperatives in urban and rural settings, and discusses adaptation and resilience mechanisms against an increased global focus on environmental conservation. The sector’s transition to sustainable development as a strategic imperative is examined. The urban-rural dichotomy reveals contrasting challenges: urban units face consumer-driven competition, while rural units face resource constraints and infrastructure deficits. Empirical studies suggest that regional development has a complex impact on the economic and environmental contours of the sector. The study uses a structured Likert scale questionnaire to measure environmental attitudes and practices within the sector. Data from companies were analysed using SPSS, revealing urban-rural differences in environmental commitment. Hierarchical roles within firms further delineate divergent perceptions of environmental action. The findings suggest an educational gap on environmental issues within the sector, coupled with a recognition of the urgency of more profound environmental action. The data also reflect scepticism about the current effectiveness of recycling and waste management, with varying perceptions of environmental threats. The research argues for stratified, context-specific sustainability interventions that take into account the diverse environmental perceptions of the sector and the specific socio-economic realities of Romanian localities.